Membaca Masa Depan Generasi Millenial; Analisis Dengan Pendekatan Fenimisme - Muhammad Rizal Fazri (Jurnal Community, 2019)
This paper examines how the millennial generation faces social challenges in the future. This study uses a feminist approach. In the perspective of feminism, there are two terms that describe the activity space for women, namely domestic and public. Domestic space encompasses women's activities related to the household, while public space involves women's activities outside the home, both in interaction with the surrounding community and in the work environment. The challenge for the next millennial generation is equal rights between men and women, in the view of feminism focusing on equal rights, women's participation in work, education, sexual freedom, and reproductive rights. Feminists in the millennial generation today also tend to become "icons" in the mass media. As Laura Mulvey, said women have become icons in the mass media. Women's bodies are used as art, so they are freely displayed and explored. The beauty and beauty of women are depicted in various photographs, paintings, various sculptures, poems, and various literary works. Various images of these women are displayed in many places, in bedrooms, living rooms, art galleries, offices, self-service hotels, salons, even workshops and on the streets. The determinism of women and the formation of social class in the analysis of capital, women become part of the social reality that is included in the analysis that is subordinated to capitalism. That is why socialist feminists emerged to create an equal position with the interests of capital and power.